The use of herbs in malaria treatment in parts of Imo State, Nigeria - Ukaga, CN; Nwoke, BEB; Onyeka, PIK; Anosike, JC; Udujih, OS; Udijih, OG; Obilor, RC; Nwachukwu, MI (Tanzania Journal of Health Research, 2009)
No Abstract.